Hubungan Riwayat Curettage dengan Kejadian Retensio Plasenta - Prasiwi Rizky Alfitri; Gumiarti Gumiarti; Eni Subiastutik (ARTERI : Jurnal Ilmu Kesehatan, 2022)
Retained placenta is the unborn placenta after 30 minutes of the childbirth. Factors that cause retained placenta include maternal age, parity, curettage history, history of cesarean section, history of endometritis, and placenta previa. According to WHO, retained placenta was the factor that contributed 15-20% of maternal mortality rate. In Indonesia, the incidence of retained placenta in 2015 was 40.3%. In East Java itself, the incidence was 53.7% in 2015. Furthermore, in the Hospital of Permata Bunda Malang City, the incidence was 30.7% in January 2018 alone. The aim of the study was to determine the relationship between curettage history and the incidence of retained placenta of birth mothers in the Hospital of Permata Bunda, Malang City. This study used a Correlation design with Cross- sectional approach. The population in this study were 95 mothers with a sample of 76 respondents who delivered the baby normally. The sampling technique implemented was the Simple Random Sampling. The method of data analysis was Chi-square analysis. Based on the result, it was found that 35 responden (46.1%) had a history of curettage, 39 respondents (51.3%) had retained placenta, and 26 respondents (34.2%) who had curettage history had retained placenta. The result of Chi-square analysis demonstrated p-value 0,001 (< α 0,05). Therefore, it can be concluded that there was a significant relationship between curettage history and the incidence of retained placenta.